Thermoplastic polyamide acid and polyimide composite film and preparation method thereof

By introducing residues derived from benzoheterocyclic diamine and flexible diamine into the polyamic acid, a stacked polyimide composite film is formed, which solves the problems of low peel strength, large expansion coefficient and high moisture absorption rate in the flexible printed circuit, and achieves the effects of low moisture absorption, low expansion coefficient and high peel strength.

CN119684601APending Publication Date: 2025-03-25INST OF ADVANCED TECH UNIV OF SCI & TECH OF CHINA +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411713102.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the field of flexible printed circuits, polyimide composite films have problems such as low peel strength, large expansion coefficient and high moisture absorption rate, which leads to easy generation of bubbles or peeling during high-temperature processing, affecting its application performance.

Method used

By introducing benzoheterocyclic diamine-derived residues with low hygroscopicity, ultra-low CTE value, excellent dimensional stability and physical properties into the structure of the thermoplastic polyamic acid, and a flexible diamine-derived residues with high peel strength, a polyimide composite film of a first thermoplastic polyimide layer, a thermoset polyimide layer and a second thermoplastic polyimide layer that are stacked in sequence.

Benefits of technology

The polyimide composite film has achieved low moisture absorption rate, low thermal expansion coefficient and high peel strength, which meets the performance requirements of double-layer FCCL, and solves the problems of separation and separation with copper foil, mismatch of thermal expansion coefficient, and bubbles or peeling during high-temperature processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684601A_ABST
    Figure CN119684601A_ABST
Patent Text Reader

Abstract

The invention provides a thermoplastic polyamide acid and polyimide composite film and a preparation method thereof, and belongs to the technical field of polyimide films. The structural general formula of the thermoplastic polyamide acid contains a repetitive structural unit as shown in a formula (I); r1 is a residue derived from first aromatic tetracid dianhydride; r2 is a residue derived from benzoheterocycle diamine, and the residue derived from benzoheterocycle diamine has one or more of structures shown in a formula (II-A)-a formula (II-C); # imgabs0 # formula (II-A); # imgabs 1 # formula (II-B); # imgabs2 formula (II-C); wherein X1, X2, X3, X4, X5 and X6 are respectively and independently selected from any one of H, F, CH3 or CF3, and Y is selected from any one of # imgabs3, # imgabs4 or # imgabs5; r3 is a residue derived from flexible diamine, and the flexible diamine contains one or more of an ether bond, a ketone bond, an alkyl carbon chain, a biphenyl bond and a thioether bond; m and n are positive integers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyimide films, and in particular to a thermoplastic polyamic acid, a polyimide composite film and a preparation method thereof. Background Art

[0002] Flexible copper clad laminate (FCCL), as an indispensable material for flexible printed circuits (FPC), has supported the rapid development of microelectronic applications in recent years and has received widespread attention. Polyimide (PI) is a good candidate for FCCL substrate film materials because of their excellent thermal, mechanical and electrical properties. There are usually three-layer and two-layer FCCLs. Among them, the three-layer FCCL is composed of copper, an organic adhesion promoter (such as epoxy resin) and a PI film. However, due to the weak heat resistance and relatively low dimensional stability of organic adhesives, the three-layer FCCL has major defects in thermal stability. In order to solve these problems, a two-layer FCCL without any adhesive was developed. The requirements for the performance of the PI film for the two-layer FCCL application are quite strict, including low hygroscopicity, low coefficient of thermal expansion (CTE value) and high peel strength.

[0003] However, in the related art, the PI film has the problems of low peel strength, large expansion coefficient and high moisture absorption rate. Summary of the invention

[0004] In view of this, the present invention provides a thermoplastic polyamic acid, polyimide composite film and a preparation method thereof.

[0005] According to an embodiment of one aspect of the present invention, a thermoplastic polyamic acid is provided, wherein the general structural formula of the thermoplastic polyamic acid contains a repeating structural unit represented by formula (I);

[0006] Formula (I);

[0007] R1 is a residue derived from a first aromatic tetraacid dianhydride;

[0008] R2 is a residue derived from benzoheterocyclic diamine, wherein the residue derived from benzoheterocyclic diamine has one or more structures represented by formula (II-A) to formula (II-C);

[0009] Formula (II-A);

[0010] Formula (II-B);

[0011] Formula (II-C);

[0012] Wherein, X1, X2, X3, X4, X5, and X6 are each independently selected from any one of H, F, CH3, or CF3, and Y is selected from , or Any of the following:

[0013] R3 is a residue derived from a flexible diamine, wherein the flexible diamine contains one or more of an ether bond, a ketone bond, an alkyl carbon chain, a biphenyl bond and a thioether bond;

[0014] m and n are positive integers.

[0015] According to another embodiment of the present invention, a method for preparing a polyimide composite film is provided, the method comprising the following steps:

[0016] Sequentially forming a first thermoplastic polyamic acid layer, a thermosetting polyamic acid layer and a second thermoplastic polyamic acid layer on the surface of the substrate to obtain a composite layer;

[0017] imidizing the composite layer to obtain a polyimide composite film;

[0018] Wherein, the first thermoplastic polyamic acid layer and the second thermoplastic polyamic acid layer independently include the thermoplastic polyamic acid.

[0019] According to another embodiment of the present invention, there is provided a polyimide composite film, the polyimide composite film comprising a first thermoplastic polyimide layer, a thermosetting polyimide layer and a second thermoplastic polyimide layer stacked in sequence;

[0020] Wherein, the general structural formulas of the first thermoplastic polyimide layer and the second thermoplastic polyimide layer independently contain a repeating structural unit represented by formula (III);

[0021] Formula (III);

[0022] R1 is a residue derived from a first aromatic tetraacid dianhydride;

[0023] R2 is a residue derived from benzoheterocyclic diamine, wherein the residue derived from benzoheterocyclic diamine has one or more structures represented by formula (II-A) to formula (II-C);

[0024] Formula (II-A);

[0025] Formula (II-B);

[0026] Formula (II-C);

[0027] Wherein, X1, X2, X3, X4, X5, and X6 are each independently selected from any one of H, F, CH3, or CF3, and Y is selected from , or Any of the following:

[0028] R3 is a residue derived from a flexible diamine, wherein the flexible diamine contains one or more of an ether bond, a ketone bond, an alkyl carbon chain, a biphenyl bond and a thioether bond;

[0029] m and n are positive integers.

[0030] According to another embodiment of the present invention, there is provided a polyimide composite film prepared by the above preparation method or the application of the above polyimide composite film in the field of flexible printed circuits.

[0031] According to an embodiment of the present invention, by introducing a benzoheterocyclic group (benzoheterocyclic diamine-derived residue) having low hygroscopicity, an ultra-low CTE value, excellent dimensional stability and physical properties and a flexible group (flexible diamine-derived residue) having high peel strength into the structure of the thermoplastic polyamic acid, the thermoplastic polyamic acid can have a higher adhesion to a metal (such as copper foil) while maintaining a lower moisture absorption rate and a higher thermal dimensional stability.

[0032] According to an embodiment of the present invention, a first thermoplastic polyamic acid layer, a thermosetting polyamic acid layer and a second thermoplastic polyamic acid layer are sequentially formed on the surface of a substrate to obtain a composite layer; the composite layer is then imidized to obtain a polyimide composite film, and the prepared polyimide composite film has low moisture absorption rate, low thermal expansion coefficient and high peel strength. The preparation method provided by the embodiment of the present invention is simple, stable in process, highly reproducible, low in energy consumption and highly economical.

[0033] The polyimide composite film provided by the embodiment of the present invention comprises a first thermoplastic polyimide layer, a thermosetting polyimide layer and a second thermoplastic polyimide layer stacked in sequence. By introducing a flexible group (a residue derived from a flexible diamine), the physical entanglement between the first thermoplastic polyimide layer, the second thermoplastic polyimide layer and the metal (such as copper foil) can be improved, thereby improving the peel strength; by introducing a benzoheterocyclic group (a residue derived from benzoheterocyclic diamine), it can form a complex with an electron-deficient Lewis acid, such as a metal cation, to further improve the peel strength. In addition, the residue derived from benzoheterocyclic diamine also has low hygroscopicity, ultra-low CTE value, excellent dimensional stability and physical properties. The first thermoplastic polyimide layer and the second thermoplastic polyimide layer of the surface layer enable the polyimide composite film to have a higher peel strength and lower hygroscopicity, and have a relatively low thermal expansion coefficient; the middle thermosetting polyimide layer has a higher dimensional stability, which further reduces the thermal expansion coefficient of the polyimide composite film. The polyimide composite film provided by the embodiment of the present invention has low hygroscopicity, low thermal expansion coefficient and high peel strength.

[0034] The polyimide composite film provided in the embodiment of the present invention is applied to the field of flexible printed circuits, which can meet the performance requirements of double-layer FCCL and solve the problems of easy delamination between the polyimide composite film and the copper foil, mismatch in thermal expansion coefficients, and easy generation of bubbles or peeling during high-temperature processing. DETAILED DESCRIPTION

[0035] Below, embodiments of the present invention will be described. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In the following detailed description, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of embodiments of the present invention. However, it is apparent that one or more embodiments may also be implemented without these specific details. In addition, in the following description, descriptions of known structures and technologies are omitted to avoid unnecessary confusion of concepts of the present invention.

[0036] The terms used herein are only for describing specific embodiments and are not intended to limit the present invention. The term "comprising" used herein indicates the existence of features, steps, operations, but does not exclude the existence or addition of one or more other features.

[0037] In the case of using expressions such as "at least one of A, B, and C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, and C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.). In the case of using expressions such as "at least one of A, B, or C, etc.", it should generally be interpreted in accordance with the meaning of the expression generally understood by those skilled in the art (for example, "a system having at least one of A, B, or C" should include but is not limited to a system having A alone, B alone, C alone, A and B, A and C, B and C, and / or A, B, C, etc.).

[0038] In the related art, due to the problem of low peel strength, the polyimide composite film is prone to delamination between the polyimide composite film and the copper foil during the subsequent use of the printed circuit board; in addition, due to the greater flexibility of the polyimide molecular chain, its thermal expansion coefficient is larger, resulting in the mismatch between the overall thermal expansion coefficient of the polyimide composite film and the copper foil, causing some processing problems such as delamination in the production process of downstream products of the printed circuit board. When the water absorption rate of the polyimide composite film is higher than 2%, the flexible copper-clad laminate will produce bubbles or peeling when subjected to high temperatures of 250 to 300°C during the graphic production process, and also cause the dimensional stability of the film to change, which seriously restricts its application in specific fields.

[0039] Among them, the coefficient of thermal expansion is one of the key parameters of PI-based FCCL. Especially in double-layer FCCL, the coefficient of thermal expansion (CTE) value of the PI base film must be precisely controlled to match the thermal expansion coefficient of the copper layer (CTE = 17 ppm K −1 ) is almost the same value. Otherwise, the FCCL may curl, which may damage the long-term reliability of the device. In related technologies, the CTE value of PI film is much higher (usually 40~80 ppm K −1 ), and therefore is not applicable.

[0040] In the process of implementing the present invention, it was found that one way to reduce the CTE value is to select a PI system composed of a rod-like backbone structure. However, PIs with a rigid rod-like conformation generally have inherently poor adhesion properties. In order to balance thermal stability and good adhesion properties, mixing a rod-like polymer system with a flexible polymer is a method to obtain the desired combination of properties. However, the inherent phase separation tendency between the rod-like and flexible polymers always leads to a decrease in the overall performance of the PI film.

[0041] In the process of realizing the present invention, it was also found that it is possible to try to develop a rigid rod-shaped PI containing special functional groups to form a complex with copper. However, polymers containing benzimidazole units generally show a high affinity for water. Even after drying in a vacuum oven for several days, up to 5% of water is retained in the polymer. When the water absorption rate is higher than 2%, bubbles or peeling will occur when the FCCL is subjected to a high temperature of 250 to 300°C during the patterning process, and the dimensional stability of the film will also change. This makes this PI less attractive in double-layer FCCL applications.

[0042] Therefore, it is necessary to develop a polyimide composite film having low moisture absorption rate, low thermal expansion coefficient and high peel strength for use in flexible printed circuit boards.

[0043] Among them, polyamic acid is the precursor material of polyimide and has an important influence on the performance and application of polyimide.

[0044] In the process of realizing the concept of the present invention, it is found that by introducing a rigid group containing a benzoheterocycle into polyamic acid, the hygroscopicity and thermal expansion coefficient of polyamic acid can be reduced; by introducing a flexible group into polyamic acid, the adhesion of polyamic acid can be improved.

[0045] Specifically, according to an embodiment of one aspect of the present invention, a thermoplastic polyamic acid is provided, wherein the general structural formula of the thermoplastic polyamic acid contains a repeating structural unit represented by formula (I);

[0046] Formula (I);

[0047] R1 is a residue derived from a first aromatic tetraacid dianhydride;

[0048] R2 is a residue derived from benzoheterocyclic diamine, and the residue derived from benzoheterocyclic diamine has one or more structures represented by formula (II-A) to formula (II-C);

[0049] Formula (II-A);

[0050] Formula (II-B);

[0051] Formula (II-C);

[0052] Wherein, X1, X2, X3, X4, X5, and X6 are each independently selected from any one of H, F, CH3, or CF3, and Y is selected from , or Any of the following:

[0053] R3 is a residue derived from a flexible diamine, wherein the flexible diamine contains one or more of an ether bond, a ketone bond, an alkyl carbon chain, a biphenyl bond, and a thioether bond;

[0054] m and n are positive integers.

[0055] According to an embodiment of the present invention, according to an embodiment of the present invention, by introducing a benzoheterocyclic group (benzoheterocyclic diamine-derived residue) having low hygroscopicity, an ultra-low CTE value, excellent dimensional stability and physical properties and a flexible group (flexible diamine-derived residue) having high peel strength into the structure of the thermoplastic polyamic acid, the thermoplastic polyamic acid can have a higher adhesion to a metal (such as copper foil) while maintaining a lower moisture absorption rate and a higher thermal dimensional stability.

[0056] According to an embodiment of the present invention, the residue derived from benzoheterocyclic diamine has one or more structures shown in formula (II-1) to formula (II-12):

[0057] Formula (II-1),

[0058] Formula (II-2),

[0059] Formula (II-3),

[0060] Formula (II-4),

[0061] Formula (II-5),

[0062] Formula (II-6),

[0063] Formula (II-7),

[0064] Formula (II-8),

[0065] Formula (II-9),

[0066] Formula (II-10),

[0067] Formula (II-11),

[0068] Formula (II-12).

[0069] According to an embodiment of the present invention, the molar ratio of the residue derived from benzoheterocyclic diamine to the residue derived from the flexible diamine is (1-9):(1-9), preferably 1:(1-9). Specifically, the molar ratio of the residue derived from benzoheterocyclic diamine to the residue derived from the flexible diamine may be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 3:7, preferably 1:4.

[0070] According to the embodiments of the present invention, the molar ratio of the residue derived from benzoheterocyclic diamine to the residue derived from the flexible diamine can make the thermoplastic polyamic acid have higher peel strength, lower thermal expansion coefficient and lower hygroscopicity.

[0071] The present invention does not limit the molar ratio of the sum of the residues derived from benzoheterocyclic diamine and the residues derived from the flexible diamine to the residues derived from the first aromatic tetraacid dianhydride. Preferably, the molar ratio of the sum of the residues derived from benzoheterocyclic diamine and the residues derived from the flexible diamine to the residues derived from the first aromatic tetraacid dianhydride is 1:(0.9-1.2).

[0072] According to an embodiment of the present invention, the flexible diamine is selected from one or more of 3,4-diaminodiphenyl ether, 3,3′-diaminodiphenyl ether, 4,4′-diaminodiphenyl ether, 2,2-bis[4-(4-aminophenoxyphenyl)]propane, all-meta-triphenyl diether diamine, 1,3-bis(4′-aminophenoxy)benzene, 3,5-diamino-4′-phenylynyl benzophenone, N,N′-diphenylbenzene diamine, 3,3′-diaminobenzophenone, 4,4′-diaminodiphenyl difluoromethane, 2,2-bis(4-aminobenzene)-propane, bis(4-(3-aminophenoxy)phenyl)sulfide, 4,4′-diaminodiphenyl sulfide, 3,4′-diaminodiphenyl sulfide and bis(4-(3-aminophenoxy)phenyl)sulfone.

[0073] According to an embodiment of the present invention, a suitable flexible diamine-derived residue can be combined with a benzoheterocyclic diamine-derived residue, and the two work together to ensure a lower thermal expansion coefficient and lower hygroscopicity, and also give the thermoplastic polyamic acid a higher peel strength.

[0074] According to an embodiment of the present invention, the first aromatic tetracarboxylic dianhydride is selected from one or more of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, butanetetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 4,4'-hexafluoroisopropylphthalic anhydride, dibenzophenone tetracarboxylic dianhydride, bisphenol A type diether dianhydride, isomellitic dianhydride, 4,4'-oxydiphthalic anhydride and triphenyl bisether dianhydride.

[0075] According to an embodiment of the present invention, a suitable first aromatic tetraacid dianhydride derived residue can be combined with a flexible diamine derived residue and a benzoheterocyclic diamine derived residue, and the three together can make the polyamic acid have higher peel strength, lower thermal expansion coefficient and lower hygroscopicity.

[0076] In the process of realizing the concept of the present invention, it is also found that through the hierarchical design of the polyimide composite film and the introduction of specific flexible groups and rigid groups in the polyimide surface layer, the polyimide composite film can have high peel strength, low thermal expansion coefficient and low hygroscopicity.

[0077] According to an embodiment of another aspect of the present invention, a method for preparing a polyimide composite film is provided, the preparation method comprising the following steps: forming a first thermoplastic polyamic acid layer, a thermosetting polyamic acid layer and a second thermoplastic polyamic acid layer in sequence on a surface of a substrate to obtain a composite layer; imidizing the composite layer to obtain a polyimide composite film; wherein the first thermoplastic polyamic acid layer and the second thermoplastic polyamic acid layer each independently include the above-mentioned thermoplastic polyamic acid.

[0078] According to an embodiment of the present invention, a first thermoplastic polyamic acid layer, a thermosetting polyamic acid layer and a second thermoplastic polyamic acid layer are sequentially formed on the surface of a substrate to obtain a composite layer; the composite layer is then imidized to obtain a polyimide composite film, and the prepared polyimide composite film has low moisture absorption rate, low thermal expansion coefficient and high peel strength. The preparation method provided by the embodiment of the present invention is simple, stable in process, highly reproducible, low in energy consumption and highly economical.

[0079] Specifically, a first thermoplastic polyamic acid layer, a thermosetting polyamic acid layer and a second thermoplastic polyamic acid layer are sequentially formed on the surface of a substrate to obtain a composite layer, which includes: preparing a first thermoplastic polyamic acid solution, a thermosetting polyamic acid solution and a second thermoplastic polyamic acid solution respectively; coating the first thermoplastic polyamic acid solution on the substrate, heating up to remove the residual solution, and forming a single self-supporting layer; coating the thermosetting polyamic acid solution on the single self-supporting layer, heating up to remove the residual solution, and obtaining a double self-supporting layer; coating the second thermoplastic polyamic acid solution on the double self-supporting layer, heating up to remove the residual solution, and obtaining three self-supporting layers, i.e., the composite layer.

[0080] According to an embodiment of the present invention, the viscosity of the first thermoplastic polyamic acid solution, the thermosetting polyamic acid solution and the second thermoplastic polyamic acid solution is independently 20000-100000 mPa·s, and the solid concentration is independently 12-30 wt %.

[0081] According to an embodiment of the present invention, the first thermoplastic polyamic acid solution is coated on the substrate, and the thickness of the formed coating can be 30-80 μm. The thermosetting polyamic acid solution is coated on the single self-supporting layer, and the thickness of the formed coating can be 100-120 μm. The second thermoplastic polyamic acid solution is coated on the double self-supporting layer, and the thickness of the formed coating can be 30-80 μm.

[0082] According to an embodiment of the present invention, the above-mentioned heating to remove the residual solution can be carried out by drying in the range of 60-200°C to remove the residual solution. Preferably, it can be baked at a temperature of 60-120°C for 10-60 min, and then baked at a temperature of 120-180°C for 10-60 min. Appropriate heating and drying methods can obtain a dry and tightly fitting three self-supporting layers (i.e., a composite layer).

[0083] According to an embodiment of the present invention, the first thermoplastic polyamic acid solution can be prepared by the following method: copolymerizing benzoheterocyclic diamine, flexible diamine and first aromatic tetraacid dianhydride to obtain a thermoplastic polyamic acid solution. Specifically, the benzoheterocyclic diamine and flexible diamine can be dissolved in a polar solvent, and then the first aromatic tetraacid dianhydride is added to react to obtain the thermoplastic polyamic acid solution.

[0084] According to an embodiment of the present invention, the benzoheterocyclic diamine is selected from one or more of the compounds shown in formula (IV-A) to formula (IV-C):

[0085] Formula (IV-A);

[0086] Formula (IV-B);

[0087] Formula (IV-C);

[0088] Wherein, X1, X2, X3, X4, X5, and X6 are each independently selected from any one of H, F, CH3, or CF3, and Y is selected from , or Any one of .

[0089] Specifically, the benzoheterocyclic diamine is selected from one or more compounds represented by formula (IV-1) to formula (IV-12):

[0090] Formula (IV-1),

[0091] Formula (IV-2),

[0092] Formula (IV-3),

[0093] Formula (IV-4),

[0094] Formula (IV-5),

[0095] Formula (IV-6),

[0096] Formula (IV-7),

[0097] Formula (IV-8),

[0098] Formula (IV-9),

[0099] Formula (IV-10),

[0100] Formula (IV-11),

[0101] Formula (IV-12).

[0102] According to an embodiment of the present invention, the molar ratio of benzoheterocyclic diamine to flexible diamine is (1-9): (1-9), preferably 1: (1-9). Specifically, the molar ratio of benzoheterocyclic diamine to flexible diamine can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 3:7, preferably 1:4.

[0103] The present invention does not limit the molar ratio of the sum of the benzoheterocyclic diamine and the flexible diamine to the first aromatic tetraacid dianhydride. Preferably, the molar ratio of the sum of the benzoheterocyclic diamine and the flexible diamine to the first aromatic tetraacid dianhydride may be 1:(0.9-1.2). Specifically, the molar ratio of the sum of the benzoheterocyclic diamine and the flexible diamine to the first aromatic tetraacid dianhydride may be 1:0.9, 1:1, 1:1.1 or 1:1.2.

[0104] The present invention does not limit the time for the copolymerization reaction of benzoheterocyclic diamine, flexible diamine and the first aromatic tetraacid dianhydride. Preferably, the copolymerization reaction time of benzoheterocyclic diamine, flexible diamine and the first aromatic tetraacid dianhydride is 3 to 72 hours, and more preferably 8 to 15 hours. Specifically, the copolymerization reaction time of benzoheterocyclic diamine, flexible diamine and the first aromatic tetraacid dianhydride can be 3 hours, 5 hours, 8 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, 30 hours, 40 hours, 50 hours, 60 hours, 70 hours or 72 hours.

[0105] According to an embodiment of the present invention, the polar solvent is a well-known solvent, which may include at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, acetonitrile, hexamethylphosphoramide, hexamethylphosphoric triamide, and N-methylpyrrolidone, preferably a high-boiling polar aprotic solvent, such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone. The amount of the polar solvent can be set according to the viscosity required by the first thermoplastic polyamic acid solution on the basis of being able to dissolve the aromatic benzoheterocyclic diamine and the flexible diamine.

[0106] According to an embodiment of the present invention, a suitable molar ratio of the sum of benzoheterocyclic diamine and flexible diamine to the first aromatic tetraacid dianhydride, and the copolymerization time of benzoheterocyclic diamine, flexible diamine and the first aromatic tetraacid dianhydride can obtain a first thermoplastic polyamic acid with a higher yield.

[0107] According to an embodiment of the present invention, during the copolymerization reaction, the raw materials can be added in batches to control the viscosity of the reaction system to avoid explosion and thus prevent coating failure in the later stage.

[0108] The preparation method of the second thermoplastic polyamic acid solution is similar to that of the first thermoplastic polyamic acid solution, and will not be described in detail. It should be noted that the second thermoplastic polyamic acid solution may be the same as or different from the first thermoplastic polyamic acid solution.

[0109] According to an embodiment of the present invention, the thermosetting polyamic acid layer contains thermosetting polyamic acid, and the thermosetting polyamic acid is prepared by copolymerization of an aromatic diamine and a second aromatic tetraacid dianhydride; specifically, the aromatic diamine can be dissolved in a polar solvent, and then the second aromatic tetraacid dianhydride is added to react.

[0110] Among them, the aromatic diamine is selected from at least one of 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, p-phenylenediamine, m-phenylenediamine, 2,2'-bis(trifluoromethyl)diaminobiphenyl, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis[4-(4-aminophenoxyphenyl)]propane, 4,4'-diamino-2,2'-dimethyl-1,1'-biphenyl and 1,3-bis(4'-aminophenoxy)benzene.

[0111] The second aromatic tetraacid dianhydride includes one or more of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, pyrophthalic acid dianhydride, p-phenylene-diphthalic acid dianhydride, bisphenol A type diether dianhydride, 4,4'-oxydiphthalic anhydride, hexafluoro dianhydride, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoro dianhydride, 3,3',4,4'-diphenylsulfone tetracarboxylic acid dianhydride and 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride.

[0112] The present invention does not limit the molar ratio of the aromatic diamine to the second aromatic tetraacid dianhydride. Preferably, the molar ratio of the aromatic diamine to the second aromatic tetraacid dianhydride may be 1:(0.9-1.2). Specifically, the molar ratio of the aromatic diamine to the second aromatic tetraacid dianhydride may be 1:0.9, 1:1, 1:1.1 or 1:1.2.

[0113] The present invention does not limit the time for the copolymerization reaction of the aromatic diamine and the second aromatic tetraacid dianhydride. Preferably, the copolymerization reaction time of the aromatic diamine and the second aromatic tetraacid dianhydride is 3 to 72 hours, and more preferably 8 to 15 hours. Specifically, the copolymerization reaction time of the aromatic diamine and the second aromatic tetraacid dianhydride can be 3 hours, 5 hours, 8 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, 30 hours, 40 hours, 50 hours, 60 hours, 70 hours or 72 hours.

[0114] Among them, the polar solvent can be selected from well-known solvents, for example, it can include one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, acetonitrile, hexamethylphosphoramide, hexamethylphosphoric triamide, and N-methylpyrrolidone, preferably a polar aprotic solvent with a high boiling point, such as one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

[0115] According to the embodiment of the present invention, a thermosetting polyamic acid solution with a relatively high viscosity can be obtained by using a suitable molar ratio of the aromatic diamine to the second aromatic tetraacid dianhydride and a copolymerization reaction time.

[0116] According to an embodiment of the present invention, after the composite layer is imidized, the coating formed by coating the first thermoplastic polyamic acid solution is a first thermoplastic polyimide layer, the coating formed by coating the thermosetting polyamide triacid solution is a thermosetting polyimide layer, and the coating formed by coating the second thermoplastic polyamic acid solution is a second thermoplastic polyimide layer.

[0117] The present invention does not limit the imidization method, which may be thermal imidization or a combination of thermal imidization and chemical imidization.

[0118] When thermal imidization is used, the heating method is not limited, and constant temperature heating, staged heating, or uniform heating can be selected as needed. Preferably, the imidization process can be completed by baking at a temperature of 280-400° C. for 10-60 min.

[0119] When a combination of thermal imidization and chemical imidization is adopted, the thermosetting polyamic acid solution and the curing agent can be evenly mixed before coating, and the weight ratio of the thermosetting polyamic acid solution to the curing agent can be 10: (3~5).

[0120] Among them, the curing agent can be obtained by dissolving a dehydrating agent and an imidizing agent in an organic solvent. Preferably, the dehydrating agent can be at least one of trifluoroacetic anhydride, acetic anhydride, and propionic anhydride. The imidizing agent can be at least one of pyridine, p-pyrroline, dimethyl pyridine, trimethyl pyridine, and quinoline. The organic solvent can be at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, acetonitrile, hexamethylphosphoramide, hexamethylphosphoric triamide, and N-methylpyrrolidone. The weight ratio of the dehydrating agent, the imidizing agent, and the polar solvent can be 1: (2-6): (3-7), preferably 1:4:5.

[0121] According to an embodiment of the present invention, the first thermoplastic polyamic acid solution, the thermosetting polyamic acid solution and the second thermoplastic polyamic acid solution may be prepared in air or in a protective atmosphere, wherein the protective atmosphere may be nitrogen, helium or the like.

[0122] According to another embodiment of the present invention, there is provided a polyimide composite film, the polyimide composite film comprising a first thermoplastic polyimide layer, a thermosetting polyimide layer and a second thermoplastic polyimide layer stacked in sequence;

[0123] Wherein, the general structural formulas of the first thermoplastic polyimide layer and the second thermoplastic polyimide layer each independently contain a repeating structural unit represented by formula (III);

[0124] Formula (III);

[0125] R1 is a residue derived from a first aromatic tetraacid dianhydride;

[0126] R2 is a residue derived from benzoheterocyclic diamine, and the residue derived from benzoheterocyclic diamine has one or more structures represented by formula (II-A) to formula (II-C);

[0127] Formula (II-A);

[0128] Formula (II-B);

[0129] Formula (II-C);

[0130] Wherein, X1, X2, X3, X4, X5, and X6 are each independently selected from any one of H, F, CH3, or CF3, and Y is selected from , or Any of the following:

[0131] R3 is a residue derived from a flexible diamine, wherein the flexible diamine contains one or more of an ether bond, a ketone bond, an alkyl carbon chain, a biphenyl bond, and a thioether bond;

[0132] m and n are positive integers.

[0133] The polyimide composite film provided by the embodiment of the present invention comprises a first thermoplastic polyimide layer, a thermosetting polyimide layer and a second thermoplastic polyimide layer stacked in sequence. By introducing a flexible group (a residue derived from a flexible diamine), the physical entanglement between the first thermoplastic polyimide layer, the second thermoplastic polyimide layer and the metal (such as copper foil) can be improved, thereby improving the peel strength; by introducing a benzoheterocyclic group (a residue derived from benzoheterocyclic diamine), it can form a complex with an electron-deficient Lewis acid, such as a metal cation, to further improve the peel strength. In addition, the residue derived from benzoheterocyclic diamine also has low hygroscopicity, ultra-low CTE value, excellent dimensional stability and physical properties. The first thermoplastic polyimide layer and the second thermoplastic polyimide layer of the surface layer enable the polyimide composite film to have a higher peel strength and lower hygroscopicity, and have a relatively low thermal expansion coefficient; the middle thermosetting polyimide layer has a higher dimensional stability, which further reduces the thermal expansion coefficient of the polyimide composite film. The polyimide composite film provided by the embodiment of the present invention has low hygroscopicity, low thermal expansion coefficient and high peel strength.

[0134] According to an embodiment of the present invention, the thickness of the first thermoplastic polyimide layer is 5-10 μm. Specifically, the thickness of the first thermoplastic polyimide layer may be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.

[0135] According to an embodiment of the present invention, the thickness of the thermosetting polyimide layer is 10-25 μm. Specifically, the thickness of the thermosetting polyimide layer can be 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm or 25 μm.

[0136] According to an embodiment of the present invention, the thickness of the second thermoplastic polyimide layer is 5-10 μm. Specifically, the thickness of the second thermoplastic polyimide layer may be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.

[0137] According to the embodiment of the present invention, suitable thicknesses of the first thermoplastic polyimide layer, the thermosetting polyimide layer and the second thermoplastic polyimide layer can further reduce the hygroscopicity and thermal expansion coefficient of the polyimide composite film and improve its high peel strength.

[0138] According to an embodiment of the present invention, the flexible diamine is selected from one or more of 3,4-diaminodiphenyl ether, 3,3′-diaminodiphenyl ether, 4,4′-diaminodiphenyl ether, 2,2-bis[4-(4-aminophenoxyphenyl)]propane, all-meta-triphenyl diether diamine, 1,3-bis(4′-aminophenoxy)benzene, 3,5-diamino-4′-phenylynyl benzophenone, N,N′-diphenylbenzene diamine, 3,3′-diaminobenzophenone, 4,4′-diaminodiphenyl difluoromethane, 2,2-bis(4-aminobenzene)-propane, bis(4-(3-aminophenoxy)phenyl)sulfide, 4,4′-diaminodiphenyl sulfide, 3,4′-diaminodiphenyl sulfide and bis(4-(3-aminophenoxy)phenyl)sulfone.

[0139] According to an embodiment of the present invention, the first aromatic tetracarboxylic dianhydride is selected from one or more of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, butanetetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 4,4'-hexafluoroisopropylphthalic anhydride, dibenzophenone tetracarboxylic dianhydride, bisphenol A type diether dianhydride, isomellitic dianhydride, 4,4'-oxydiphthalic anhydride and triphenyl bisether dianhydride.

[0140] According to another embodiment of the present invention, there is provided a polyimide composite film prepared by the above preparation method or the application of the above polyimide composite film in the field of flexible printed circuits.

[0141] The polyimide composite film provided in the embodiment of the present invention is applied to the field of flexible printed circuits, which can meet the performance requirements of double-layer FCCL and solve the problems of easy delamination between the polyimide composite film and the copper foil, mismatch in thermal expansion coefficients, and easy generation of bubbles or peeling during high-temperature processing.

[0142] The following lists a number of specific embodiments to illustrate the technical solution of the present invention in detail. It should be noted that the specific embodiments below are only used for illustration and are not used to limit the present invention.

[0143] First, some synthesis examples of the thermoplastic polyamic acid solution and the thermosetting polyamic acid solution used in the following embodiments are given:

[0144] The raw materials used in the following synthesis examples and their brief expressions are described as follows:

[0145] A: 4,4'-diaminodiphenyl ether (ODA)

[0146] B: p-phenylenediamine (PDA)

[0147] C: 4,4'-diamino-2,2'-dimethyl-1,1'-biphenyl (m-TD)

[0148] D: 5-amino-2-(4-aminophenyl)-benzoxazole (APBOA) (benzoheterocyclic diamine having the structure shown in formula (IV-10))

[0149] E: 2,6-(4,4'-aminophenyl)-benzisoxazole (DIABO) (benzoheterocyclic diamine having the structure shown in formula (IV-1))

[0150] F: 4,4'-([6,6'-dibenzo[d]oxazole]-2,2'-diyl)diphenylamine (DAPBO) (benzoheterocyclic diamine having the structure shown in formula (IV-4))

[0151] G: 2,2'-Bis[4-(4-aminophenoxyphenyl)]propane (BAPP)

[0152] H: Biphenyltetracarboxylic dianhydride (s-BPDA)

[0153] I: Pyromellitic dianhydride (PMDA)

[0154] J: 4,4'-oxydiphthalic anhydride (ODPA)

[0155] K: 3,3',4,4'-Benzophenonetetracarboxylic dianhydride (BTDA)

[0156] L: N,N-dimethylacetamide

[0157] Example 1

[0158] This embodiment provides a thermoplastic polyamic acid, the general structural formula of which contains the repeating structural unit shown in the above formula (I), wherein R1 is a residue derived from compound H, R2 is a residue derived from compound D, and R3 is a residue derived from compound A.

[0159] This embodiment also provides a method for preparing the thermoplastic polyamic acid, comprising the following steps:

[0160] In a 250 mL three-necked flask equipped with a temperature-controlled water bath and a stirring device, 80 mmol of compound A, 20 mmol of compound D and a polar solvent L were added, and the mixture was stirred at 25°C until the solid was completely dissolved. Then, 95 mmol of compound H was slowly added to the system and stirred for 1 hour to dissolve it. Finally, 5 mmol of compound H was slowly added to the reaction solution. When the viscosity reached about 20,000 mPa·s, the addition was stopped, and stirring was continued for 10 hours to obtain a thermoplastic polyamic acid solution 1 having a solid concentration of 20 wt% and a rotational viscosity of 50,000 mPa·s at 25°C.

[0161] Example 2

[0162] This embodiment provides a thermoplastic polyamic acid, the general structural formula of which contains the repeating structural unit shown in the above formula (I), wherein R1 is a residue derived from compound H and compound I, R2 is a residue derived from compound D, and R3 is a residue derived from compound A.

[0163] This embodiment also provides a method for preparing the thermoplastic polyamic acid, comprising the following steps:

[0164] In a 250 mL three-necked flask equipped with a temperature-controlled water bath and a stirring device, 80 mmol of compound A, 20 mmol of compound D and a polar solvent L were added, and the mixture was stirred at 25°C until the solid was completely dissolved. Then, 10 mmol of compound H was slowly added to the system and stirred for 1 h to dissolve it. Then, 85 mmol of compound I was slowly added to the reaction solution, and finally, 5 mmol of compound I was slowly added to the reaction solution. When the viscosity reached about 20,000 mPa·s, the addition was stopped and stirring was continued for 10 h to obtain a thermoplastic polyamic acid solution 2 having a solid concentration of 20 wt% and a rotational viscosity of 50,000 mPa·s at 25°C.

[0165] Example 3

[0166] This embodiment provides a thermoplastic polyamic acid, the general structural formula of which contains the repeating structural unit shown in the above formula (I), wherein R1 is a residue derived from compound J, R2 is a residue derived from compound D, and R3 is a residue derived from compound A.

[0167] This embodiment also provides a method for preparing the thermoplastic polyamic acid, comprising the following steps:

[0168] In a 250 mL three-necked flask equipped with a temperature-controlled water bath and a stirring device, 80 mmol of compound A, 20 mmol of compound D and a polar solvent L were added. After stirring at 25°C until the solid was completely dissolved, 95 mmol of compound J was slowly added to the system and stirred for 1 h to dissolve it. Finally, 5 mmol of compound J was slowly added to the reaction solution. When the viscosity reached about 20,000 mPa·s, the addition was stopped and stirring was continued for 10 h to obtain a thermoplastic polyamic acid solution 3 with a solid concentration of 20 wt% and a rotational viscosity of 50,000 mPa·s at 25°C.

[0169] Example 4

[0170] This embodiment provides a thermoplastic polyamic acid, the general structural formula of which contains the repeating structural unit shown in the above formula (I), wherein R1 is a residue derived from compound K, R2 is a residue derived from compound D, and R3 is a residue derived from compound A.

[0171] This embodiment also provides a method for preparing the thermoplastic polyamic acid, comprising the following steps:

[0172] In a 250 mL three-necked flask equipped with a temperature-controlled water bath and a stirring device, 80 mmol of compound A, 20 mmol of compound D and a polar solvent L were added. After stirring at 25°C until the solid was completely dissolved, 95 mmol of compound I was slowly added to the system and stirred for 1 h to dissolve it. Finally, 5 mmol of compound K was slowly added to the reaction solution. When the viscosity reached about 20,000 mPa·s, the addition was stopped and stirring was continued for 10 h to obtain a thermoplastic polyamic acid solution 4 with a solid concentration of 20 wt% and a rotational viscosity of 50,000 mPa·s at 25°C.

[0173] Example 5

[0174] This embodiment provides a thermoplastic polyamic acid, the general structural formula of which contains the repeating structural unit shown in the above formula (I), wherein R1 is a residue derived from compound H and compound I, R2 is a residue derived from compound D, and R3 is a residue derived from compound G.

[0175] This embodiment also provides a method for preparing the thermoplastic polyamic acid, comprising the following steps:

[0176] In a 250 mL three-necked flask equipped with a temperature-controlled water bath and a stirring device, 80 mmol of compound G, 20 mmol of compound D and a polar solvent L were added, and the mixture was stirred at 25°C until the solid was completely dissolved. Then, 10 mmol of compound H was slowly added to the system and stirred for 1 hour to dissolve it. Then, 85 mmol of compound I was slowly added to the reaction solution, and finally, 5 mmol of compound I was slowly added to the reaction solution. When the viscosity reached about 20,000 mPa·s, the addition was stopped and stirring was continued for 10 hours to obtain a thermoplastic polyamic acid solution 5 having a solid concentration of 20 wt% and a rotational viscosity of 50,000 mPa·s at 25°C.

[0177] Example 6

[0178] This embodiment provides a thermoplastic polyamic acid, the general structural formula of which contains the repeating structural unit shown in the above formula (I), wherein R1 is a residue derived from compound H and compound I, R2 is a residue derived from compound E, and R3 is a residue derived from compound G.

[0179] This embodiment also provides a method for preparing the thermoplastic polyamic acid, comprising the following steps:

[0180] In a 250 mL three-necked flask equipped with a temperature-controlled water bath and a stirring device, 80 mmol of compound G, 20 mmol of compound E and a polar solvent L were added, and the mixture was stirred at 25°C until the solid was completely dissolved. Then, 10 mmol of compound H was slowly added to the system and stirred for 1 hour to dissolve it. Then, 85 mmol of compound I was slowly added to the reaction solution, and finally, 5 mmol of compound I was slowly added to the reaction solution. When the viscosity reached about 20,000 mPa·s, the addition was stopped and stirring was continued for 10 hours to obtain a thermoplastic polyamic acid solution 6 with a solid concentration of 20 wt% and a rotational viscosity of 50,000 mPa·s at 25°C.

[0181] Example 7

[0182] This embodiment provides a thermoplastic polyamic acid, the general structural formula of which contains the repeating structural unit shown in the above formula (I), wherein R1 is a residue derived from compound H and compound I, R2 is a residue derived from compound F, and R3 is a residue derived from compound G.

[0183] This embodiment also provides a method for preparing the thermoplastic polyamic acid, comprising the following steps:

[0184] In a 250 mL three-necked flask equipped with a temperature-controlled water bath and a stirring device, 80 mmol of compound G, 20 mmol of compound F and a polar solvent L were added. After stirring at 25°C until the solid was completely dissolved, 10 mmol of compound H was slowly added to the system and stirred for 1 hour to dissolve it. Then 85 mmol of compound I was slowly added to the reaction solution. Finally, 5 mmol of compound I was slowly added to the reaction solution. When the viscosity reached about 20,000 mPa·s, the addition was stopped and stirring was continued for 10 hours to obtain a thermoplastic polyamic acid solution 7 with a solid concentration of 20 wt% and a rotational viscosity of 50,000 mPa·s at 25°C.

[0185] Example 8

[0186] The present embodiment provides a polyimide composite film, which includes a first thermoplastic polyimide layer, a thermosetting polyimide layer and a second thermoplastic polyimide layer stacked in sequence; wherein the general structural formula of the first thermoplastic polyimide layer and the second thermoplastic polyimide layer contains a repeating structural unit shown in the above formula (III), wherein R1 is a residue derived from compound H, R2 is a residue derived from compound D, and R3 is a residue derived from compound A.

[0187] This embodiment provides a method for preparing the above-mentioned polyimide composite film, comprising the following steps:

[0188] S10, preparing a thermoplastic polyamic acid solution 1 by referring to the method of Example 1.

[0189] Thermosetting polyamic acid solution 1 was prepared according to the following method:

[0190] 100 mmol of compound B and polar solvent L were added to a 250 mL three-necked flask equipped with a temperature-controlled water bath and a stirring device. After stirring at 25°C until the solid was completely dissolved, 95 mmol of compound H was slowly added to the system and stirred for 1 h to dissolve it. Finally, 5 mmol of compound H was slowly added to the reaction solution. When the viscosity reached about 20000 mPa·s, the addition was stopped and stirring was continued for 10 h to obtain a thermosetting polyamic acid solution 1 with a solid concentration of 20 wt% and a rotational viscosity of 100000 mPa·s at 25°C.

[0191] S20, coating a layer of thermoplastic polyamic acid solution 1 with a thickness of 50 μm on the tempered glass, baking it at a temperature of 120°C for 10 min, and baking it at a temperature of 150°C for 10 min to obtain a self-supporting layer; then coating a layer of thermosetting polyamic acid solution 1 with a thickness of 100 μm on the self-supporting layer, baking it at a temperature of 120°C for 10 min, baking it at a temperature of 150°C for 10 min, and drying it to obtain a double self-supporting layer, and then coating a layer of thermoplastic polyamic acid solution 1 with a thickness of 50 μm on the double self-supporting layer, baking it at a temperature of 120°C for 10 min, baking it at a temperature of 150°C for 10 min, and baking it at a temperature of 180°C for 10 min to obtain a triple self-supporting layer.

[0192] S30, baking the three self-supporting layers at 280° C. for 10 min to complete the imidization process and obtain a polyimide composite film.

[0193] Example 9

[0194] The present embodiment provides a polyimide composite film, which includes a first thermoplastic polyimide layer, a thermosetting polyimide layer and a second thermoplastic polyimide layer stacked in sequence; wherein the general structural formula of the first thermoplastic polyimide layer and the second thermoplastic polyimide layer contains a repeating structural unit shown in the above formula (III), wherein R1 is a residue derived from compound H and compound I, R2 is a residue derived from compound D, and R3 is a residue derived from compound A.

[0195] This embodiment provides a method for preparing the above-mentioned polyimide composite film, comprising the following steps:

[0196] S10, preparing a thermoplastic polyamic acid solution 2 by referring to the method in Example 2, and preparing a thermosetting polyamic acid solution 1 by referring to the method in Example 6.

[0197] S20, coating a layer of thermoplastic polyamic acid solution 2 with a thickness of 30 μm on the tempered glass, baking it at a temperature of 60°C for 60 min, and baking it at a temperature of 120°C for 60 min to obtain a self-supporting layer; then coating a layer of thermosetting polyamic acid solution 1 with a thickness of 110 μm on the self-supporting layer, baking it at a temperature of 60°C for 60 min, baking it at a temperature of 120°C for 60 min, and drying to obtain a double self-supporting layer, and then coating a layer of thermoplastic polyamic acid solution 2 with a thickness of 30 μm on the double self-supporting layer, baking it at a temperature of 60°C for 60 min, baking it at a temperature of 120°C for 60 min, and baking it at a temperature of 180°C for 60 min to obtain a triple self-supporting layer.

[0198] S30, baking the three self-supporting layers at 380° C. for 10 min to complete the imidization process and obtain a polyimide composite film.

[0199] Example 10

[0200] The present embodiment provides a polyimide composite film, which includes a first thermoplastic polyimide layer, a thermosetting polyimide layer and a second thermoplastic polyimide layer stacked in sequence; wherein the general structural formula of the first thermoplastic polyimide layer and the second thermoplastic polyimide layer contains a repeating structural unit shown in the above formula (III), wherein R1 is a residue derived from compound J, R2 is a residue derived from compound D, and R3 is a residue derived from compound A.

[0201] This embodiment provides a method for preparing the above-mentioned polyimide composite film, comprising the following steps:

[0202] S10, preparing a thermoplastic polyamic acid solution 3 by referring to the method in Example 3, and preparing a thermosetting polyamic acid solution 1 by referring to the method in Example 6.

[0203] S20, coating a layer of thermoplastic polyamic acid solution 3 with a thickness of 40 μm on the tempered glass, baking it at a temperature of 100°C for 30 min, and baking it at a temperature of 150°C for 30 min to obtain a self-supporting layer; then coating a layer of thermosetting polyamic acid solution 1 with a thickness of 120 μm on the self-supporting layer, baking it at a temperature of 100°C for 30 min, baking it at a temperature of 150°C for 30 min, and drying to obtain a double self-supporting layer, and then coating a layer of thermoplastic polyamic acid solution 3 with a thickness of 40 μm on the double self-supporting layer, baking it at a temperature of 100°C for 40 min, baking it at a temperature of 150°C for 40 min, and baking it at a temperature of 250°C for 40 min to obtain a triple self-supporting layer.

[0204] S30, baking the three self-supporting layers at 300° C. for 50 min to complete the imidization process and obtain a polyimide composite film.

[0205] Embodiment 11

[0206] The present embodiment provides a polyimide composite film, which includes a first thermoplastic polyimide layer, a thermosetting polyimide layer and a second thermoplastic polyimide layer stacked in sequence; wherein the general structural formula of the first thermoplastic polyimide layer and the second thermoplastic polyimide layer contains a repeating structural unit shown in the above formula (III), wherein R1 is a residue derived from compound K, R2 is a residue derived from compound D, and R3 is a residue derived from compound A.

[0207] This embodiment provides a method for preparing the above-mentioned polyimide composite film, comprising the following steps:

[0208] S10, preparing a thermoplastic polyamic acid solution 4 by referring to the method in Example 4, and preparing a thermosetting polyamic acid solution 1 by referring to the method in Example 6.

[0209] S20, coating a layer of thermoplastic polyamic acid solution 4 with a thickness of 60 μm on the tempered glass, baking it at a temperature of 80°C for 60 min, and baking it at a temperature of 120°C for 60 min to obtain a self-supporting layer; then coating a layer of thermosetting polyamic acid solution 1 with a thickness of 100 μm on the self-supporting layer, baking it at a temperature of 80°C for 60 min, baking it at a temperature of 150°C for 20 min, and drying to obtain a double self-supporting layer, and then coating a layer of thermoplastic polyamic acid solution 4 with a thickness of 60 μm on the double self-supporting layer, baking it at a temperature of 100°C for 50 min, baking it at a temperature of 150°C for 30 min, and baking it at a temperature of 250°C for 30 min to obtain a triple self-supporting layer.

[0210] S30, baking the three self-supporting layers at 300° C. for 10 min to complete the imidization process and obtain a polyimide composite film.

[0211] Example 12

[0212] The present embodiment provides a polyimide composite film, which includes a first thermoplastic polyimide layer, a thermosetting polyimide layer and a second thermoplastic polyimide layer stacked in sequence; wherein the general structural formula of the first thermoplastic polyimide layer and the second thermoplastic polyimide layer contains a repeating structural unit shown in the above formula (III), wherein R1 is a residue derived from compound H and compound I, R2 is a residue derived from compound D, and R3 is a residue derived from compound G.

[0213] This embodiment provides a method for preparing the above-mentioned polyimide composite film, comprising the following steps:

[0214] S10, preparing a thermoplastic polyamic acid solution 5 by referring to the method of Example 5.

[0215] Thermosetting polyamic acid solution 2 was prepared according to the following method:

[0216] In a 250 mL three-necked flask equipped with a temperature-controlled water bath and a stirring device, 80 mmol of compound B, 20 mmol of compound C and polar solvent L were added, and the mixture was stirred at 25°C until the solid was completely dissolved. Then, 95 mmol of compound H was slowly added to the system and stirred for 1 h to dissolve it. Finally, 5 mmol of compound H was slowly added to the reaction solution. When the viscosity reached about 20,000 mPa·s, the addition was stopped and stirring was continued for 10 h to obtain a thermosetting polyamic acid solution 2 with a solid concentration of 20 wt% and a rotational viscosity of 100,000 mPa·s at 25°C.

[0217] S20, coating a layer of thermoplastic polyamic acid solution 5 with a thickness of 80 μm on the tempered glass, baking it at a temperature of 80°C for 20 min, and baking it at a temperature of 160°C for 20 min to obtain a self-supporting layer; then coating a layer of thermosetting polyamic acid solution 2 with a thickness of 120 μm on the self-supporting layer, baking it at a temperature of 80°C for 20 min, baking it at a temperature of 160°C for 20 min, and drying to obtain a double self-supporting layer, and then coating a layer of thermoplastic polyamic acid solution 5 with a thickness of 70 μm on the double self-supporting layer, baking it at a temperature of 80°C for 20 min, baking it at a temperature of 160°C for 20 min, and baking it at a temperature of 280°C for 10 min to obtain a triple self-supporting layer.

[0218] S30, baking the three self-supporting layers at 380° C. for 10 min to complete the imidization process and obtain a polyimide composite film.

[0219] Example 13

[0220] The present embodiment provides a polyimide composite film, which includes a first thermoplastic polyimide layer, a thermosetting polyimide layer and a second thermoplastic polyimide layer stacked in sequence; wherein the general structural formula of the first thermoplastic polyimide layer and the second thermoplastic polyimide layer contains a repeating structural unit shown in the above formula (III), wherein R1 is a residue derived from compound H and compound I, R2 is a residue derived from compound E, and R3 is a residue derived from compound G.

[0221] This embodiment provides a method for preparing the above-mentioned polyimide composite film, comprising the following steps:

[0222] S10, preparing a thermoplastic polyamic acid solution 6 by referring to the method in Example 6, and preparing a thermosetting polyamic acid solution 2 by referring to the method in Example 12.

[0223] S20, coating a layer of thermoplastic polyamic acid solution 6 with a thickness of 80 μm on the tempered glass, baking it at a temperature of 80°C for 20 min, and baking it at a temperature of 160°C for 20 min to obtain a self-supporting layer; then coating a layer of thermosetting polyamic acid solution 2 with a thickness of 120 μm on the self-supporting layer, baking it at a temperature of 80°C for 20 min, baking it at a temperature of 160°C for 20 min, and drying it to obtain a double self-supporting layer, and then coating a layer of thermoplastic polyamic acid solution 6 with a thickness of 70 μm on the double self-supporting layer, baking it at a temperature of 80°C for 20 min, baking it at a temperature of 160°C for 20 min, and baking it at a temperature of 280°C for 10 min to obtain a triple self-supporting layer.

[0224] S30, baking the three self-supporting layers at 380° C. for 10 min to complete the imidization process and obtain a polyimide composite film.

[0225] Embodiment 14

[0226] The present embodiment provides a polyimide composite film, which includes a first thermoplastic polyimide layer, a thermosetting polyimide layer and a second thermoplastic polyimide layer stacked in sequence; wherein the general structural formula of the first thermoplastic polyimide layer and the second thermoplastic polyimide layer contains a repeating structural unit shown in the above formula (III), wherein R1 is a residue derived from compound H and compound I, R2 is a residue derived from compound F, and R3 is a residue derived from compound G.

[0227] This embodiment provides a method for preparing the above-mentioned polyimide composite film, comprising the following steps:

[0228] S10, preparing a thermoplastic polyamic acid solution 7 by referring to the method in Example 5, and preparing a thermosetting polyamic acid solution 2 by referring to the method in Example 12.

[0229] S20, coating a layer of thermoplastic polyamic acid solution 7 with a thickness of 80 μm on the tempered glass, baking it at a temperature of 80°C for 20 min, and baking it at a temperature of 160°C for 20 min to obtain a self-supporting layer; then coating a layer of thermosetting polyamic acid solution 2 with a thickness of 120 μm on the self-supporting layer, baking it at a temperature of 80°C for 20 min, baking it at a temperature of 160°C for 20 min, and drying to obtain a double self-supporting layer, and then coating a layer of thermoplastic polyamic acid solution 7 with a thickness of 70 μm on the double self-supporting layer, baking it at a temperature of 80°C for 20 min, baking it at a temperature of 160°C for 20 min, and baking it at a temperature of 280°C for 10 min to obtain a triple self-supporting layer.

[0230] S30, baking the three self-supporting layers at 380° C. for 10 min to complete the imidization process and obtain a polyimide composite film.

[0231] Comparative Example 1

[0232] This comparative example provides a thermoplastic polyamic acid, the general structural formula of which contains the repeating structural unit shown in the above formula (I), wherein R1 is a residue derived from compound H, and R2 and R3 are residues derived from compound A.

[0233] This comparative example also provides a method for preparing the above-mentioned thermoplastic polyamic acid, comprising the following steps:

[0234] 100 mmol of compound A and polar solvent L were added to a 250 mL three-necked flask equipped with a temperature-controlled water bath and a stirring device. After stirring at 25°C until the solid was completely dissolved, 90 mmol of compound H was slowly added to the system and stirred for 1 hour to dissolve it. Then 5 mmol of compound H was slowly added to the reaction solution. When the viscosity reached about 20,000 mPa·s, the addition was stopped and stirring was continued for 10 hours to obtain a thermoplastic polyamic acid solution 8 with a solid concentration of 20 wt% and a rotational viscosity of 50,000 mPa·s at 25°C.

[0235] Comparative Example 2

[0236] This comparative example provides a thermoplastic polyamic acid, the general structural formula of which contains the repeating structural unit shown in the above formula (I), wherein R1 is a residue derived from compound H, and R2 and R3 are residues derived from compound E.

[0237] This comparative example also provides a method for preparing the above-mentioned thermoplastic polyamic acid, comprising the following steps:

[0238] 100 mmol of compound E and polar solvent L were added to a 250 mL three-necked flask equipped with a temperature-controlled water bath and a stirring device. After stirring at 25°C until the solid was completely dissolved, 95 mmol of compound H was slowly added to the system and stirred for 1 h to dissolve it. Then 5 mmol of compound H was slowly added to the reaction solution. The addition was stopped when the viscosity reached about 20,000 mPa·s. Stirring was continued for 10 h to obtain a thermoplastic polyamic acid solution 9 with a solid concentration of 20 wt% and a rotational viscosity of 50,000 mPa·s at 25°C.

[0239] Comparative Example 3

[0240] This comparative example provides a polyimide composite film, which includes a first thermoplastic polyimide layer, a thermosetting polyimide layer and a second thermoplastic polyimide layer stacked in sequence; wherein the general structural formula of the first thermoplastic polyimide layer and the second thermoplastic polyimide layer contains a repeating structural unit shown in the above formula (III), wherein R1 is a residue derived from compound H, and R2 and R3 are residues derived from compound A.

[0241] The preparation method of the polyimide composite film provided in this comparative example refers to Example 8, except that the thermoplastic polyamic acid solution 1 in Example 8 is replaced with the thermoplastic polyamic acid solution 8.

[0242] Comparative Example 4

[0243] This comparative example provides a polyimide composite film, refer to comparative example 3.

[0244] The preparation method of the polyimide composite film provided in this comparative example refers to that of comparative example 3, except that the thermosetting polyamic acid solution 1 is replaced with the thermosetting polyamic acid solution 2.

[0245] Comparative Example 5

[0246] This comparative example provides a polyimide composite film, which includes a first thermoplastic polyimide layer, a thermosetting polyimide layer and a second thermoplastic polyimide layer stacked in sequence; wherein the general structural formula of the first thermoplastic polyimide layer and the second thermoplastic polyimide layer contains a repeating structural unit shown in the above formula (III), wherein R1 is a residue derived from compound H, and R2 and R3 are residues derived from compound G.

[0247] The preparation method of the polyimide composite film provided in this comparative example refers to Example 8, except that the thermoplastic polyamic acid solution 1 in Example 8 is replaced with a thermoplastic polyamic acid solution 9.

[0248] Comparative Example 6

[0249] This comparative example provides a polyimide composite film, refer to comparative example 5.

[0250] The preparation method of the polyimide composite film provided in this comparative example refers to that of comparative example 5, except that the thermosetting polyamic acid solution 1 is replaced with the thermosetting polyamic acid solution 2.

[0251] For the convenience of analysis and comparison, Table 1 shows the formulas of thermoplastic polyamic acid solutions 1 to 9 and thermosetting polyamic acid solutions 1 and 2 provided in Examples 1 to 7 and Comparative Examples 1 to 2. Table 2 shows the material selection and performance parameters of the polyimide composite films provided in Examples 8 to 14. Among them, the test method of thermal expansion coefficient refers to IPC-TM-650-2.4.41.3; the test method of peel strength refers to IPC-TM-650-2.4.8; the test method of moisture absorption rate refers to GB / T 13557-2007.

[0252] Table 1

[0253]

[0254] Table 2

[0255]

[0256] From the analysis of Table 2, it can be seen that the polyimide composite films provided by Comparative Examples 3 to 6 have a higher thermal expansion coefficient, a lower peel strength and a higher moisture absorption rate, indicating that when the first thermoplastic polyimide layer and the second thermoplastic polyimide layer do not contain benzoheterocyclic diamine, the polyimide composite film does not meet the performance requirements of the two-layer flexible copper clad laminate base film.

[0257] Compared with comparative examples 3 to 6, the polyimide composite film provided by the embodiment of the present invention has a lower thermal expansion coefficient and a higher peel strength, while maintaining a low hygroscopicity. The thermal expansion coefficient (CTE) can reach ≤17 ppm / K, and the peel strength can reach >17 N / cm film. The moisture absorption rate is maintained at <1.0%, meeting the performance requirements of the two-layer flexible copper clad laminate base film.

[0258] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent replacement, improvement, etc. made to the technical method by any technician familiar with the art within the spirit and principle of the present invention is still included in the protection scope of the technical solution of the present invention.

Claims

1. A thermoplastic polyamic acid, characterized in that: The general structural formula of the thermoplastic polyamic acid contains a repeating structural unit represented by formula (I); Formula (I); R1 is a residue derived from a first aromatic tetraacid dianhydride; R2 is a residue derived from benzoheterocyclic diamine, wherein the residue derived from benzoheterocyclic diamine has one or more structures represented by formula (II-A) to formula (II-C); Formula (II-A); Formula (II-B); Formula (II-C); Wherein, X1, X2, X3, X4, X5, and X6 are each independently selected from any one of H, F, CH3, or CF3, and Y is selected from , or Any of the following: R3 is a residue derived from a flexible diamine, wherein the flexible diamine contains one or more of an ether bond, a ketone bond, an alkyl carbon chain, a biphenyl bond, and a thioether bond; m and n are positive integers.

2. The thermoplastic polyamic acid according to claim 1, characterized in that The benzoheterocyclic diamine-derived residue has one or more structures shown in formula (II-1) to formula (II-12): Formula (II-1), Formula (II-2), Formula (II-3), Formula (II-4), Formula (II-5), Formula (II-6), Formula (II-7), Formula (II-8), Formula (II-9), Formula (II-10), Formula (II-11), Formula (II-12).

3. The thermoplastic polyamic acid according to claim 1, characterized in that The molar ratio of the residue derived from the benzoheterocyclic diamine to the residue derived from the flexible diamine is (1-9):(1-9); The molar ratio of the sum of the residue derived from the benzoheterocyclic diamine and the residue derived from the flexible diamine to the residue derived from the first aromatic tetraacid dianhydride is 1:(0.9-1.2).

4. The thermoplastic polyamic acid according to any one of claims 1 to 3, characterized in that The flexible diamine is selected from one or more of 3,4-diaminodiphenyl ether, 3,3′-diaminodiphenyl ether, 4,4′-diaminodiphenyl ether, 2,2-bis[4-(4-aminophenoxyphenyl)]propane, all-meta-triphenyl diether diamine, 1,3-bis(4′-aminophenoxy)benzene, 3,5-diamino-4′-phenyl alkynyl benzophenone, N,N′-diphenyl biphenyl diamine, 3,3′-diaminobenzophenone, 4,4′-diaminodiphenyl difluoromethane, 2,2-bis(4-aminobenzene)-propane, bis(4-(3-aminophenoxy)phenyl)sulfide, 4,4′-diaminodiphenyl sulfide, 3,4′-diaminodiphenyl sulfide and bis(4-(3-aminophenoxy)phenyl)sulfone; The first aromatic tetracarboxylic dianhydride is selected from one or more of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, butanetetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 4,4'-hexafluoroisopropylphthalic anhydride, dibenzophenone tetracarboxylic dianhydride, bisphenol A type diether dianhydride, pyromellitic dianhydride, 4,4'-oxydiphthalic anhydride and triphenyl bisether dianhydride.

5. A method for preparing a polyimide composite film, characterized in that: The preparation method comprises the following steps: Sequentially forming a first thermoplastic polyamic acid layer, a thermosetting polyamic acid layer and a second thermoplastic polyamic acid layer on the surface of the substrate to obtain a composite layer; imidizing the composite layer to obtain a polyimide composite film; Wherein, the first thermoplastic polyamic acid layer and the second thermoplastic polyamic acid layer each independently include the thermoplastic polyamic acid according to any one of claims 1 to 4.

6. The preparation method according to claim 5, characterized in that: The thermosetting polyamic acid layer contains thermosetting polyamic acid, and the thermosetting polyamic acid is prepared by copolymerization of aromatic diamine and a second aromatic tetraacid dianhydride; The aromatic diamine is selected from at least one of 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, p-phenylenediamine, m-phenylenediamine, 2,2'-bis(trifluoromethyl)diaminobiphenyl, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis[4-(4-aminophenoxyphenyl)]propane, 4,4'-diamino-2,2'-dimethyl-1,1'-biphenyl and 1,3-bis(4'-aminophenoxy)benzene; The second aromatic tetracarboxylic dianhydride includes one or more of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, p-phenylene-diphthalic acid dianhydride, bisphenol A type diether dianhydride, 4,4'-oxydiphthalic anhydride, hexafluoro dianhydride, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoro dianhydride, 3,3',4,4'-diphenylsulfone tetracarboxylic dianhydride and 3,3',4,4'-benzophenone tetracarboxylic dianhydride; The molar ratio of the aromatic diamine to the second aromatic tetracarboxylic dianhydride is 1:(0.9-1.2).

7. A polyimide composite film, characterized in that: The polyimide composite film comprises a first thermoplastic polyimide layer, a thermosetting polyimide layer and a second thermoplastic polyimide layer which are stacked in sequence; Wherein, the general structural formulas of the first thermoplastic polyimide layer and the second thermoplastic polyimide layer each independently contain a repeating structural unit represented by formula (III); Formula (III); R1 is a residue derived from a first aromatic tetraacid dianhydride; R2 is a residue derived from benzoheterocyclic diamine, wherein the residue derived from benzoheterocyclic diamine has one or more structures represented by formula (II-A) to formula (II-C); Formula (II-A); Formula (II-B); Formula (II-C); Wherein, X1, X2, X3, X4, X5, and X6 are each independently selected from any one of H, F, CH3, or CF3, and Y is selected from , or Any of the following: R3 is a residue derived from a flexible diamine, wherein the flexible diamine contains one or more of an ether bond, a ketone bond, an alkyl carbon chain, a biphenyl bond, and a thioether bond; m and n are positive integers.

8. The polyimide composite film according to claim 7, characterized in that: The thickness of the first thermoplastic polyimide layer is 5-10 μm; The thickness of the thermosetting polyimide layer is 10-25 μm; The thickness of the second thermoplastic polyimide layer is 5-10 μm.

9. The polyimide composite film according to claim 7 or 8, characterized in that: The flexible diamine is selected from one or more of 3,4-diaminodiphenyl ether, 3,3′-diaminodiphenyl ether, 4,4′-diaminodiphenyl ether, 2,2-bis[4-(4-aminophenoxyphenyl)]propane, all-meta-triphenyl diether diamine, 1,3-bis(4′-aminophenoxy)benzene, 3,5-diamino-4′-phenyl alkynyl benzophenone, N,N′-diphenyl biphenyl diamine, 3,3′-diaminobenzophenone, 4,4′-diaminodiphenyl difluoromethane, 2,2-bis(4-aminobenzene)-propane, bis(4-(3-aminophenoxy)phenyl)sulfide, 4,4′-diaminodiphenyl sulfide, 3,4′-diaminodiphenyl sulfide and bis(4-(3-aminophenoxy)phenyl)sulfone; The first aromatic tetracarboxylic dianhydride is selected from one or more of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, butanetetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 4,4-hexafluoroisopropylphthalic anhydride, dibenzophenone tetracarboxylic dianhydride, bisphenol A type diether dianhydride, pyromellitic dianhydride, 4,4'-oxydiphthalic anhydride and triphenyl bisether dianhydride.

10. Use of a polyimide composite film obtained by the preparation method according to claim 5 or 6 or a polyimide composite film according to any one of claims 7 to 9 in the field of flexible printed circuits.

Citation Information

Patent Citations

  • Process for producing layered product, layered product, process for producing layered product with device using said layered product, and layered product with device

    CN104395080A

  • Heat conduction backboard for crystalline silicon assembly, and preparation method thereof

    CN104992998A

  • Dimensionally stable type polyimide film and preparation method thereof

    CN108117654A

  • Poly (imide-benzoxazole) film as well as preparation method and application thereof

    CN111019345A

  • Photo-thermal response three-dimensional shape memory polyimide, preparation method and application thereof

    CN111303425A